2015
DOI: 10.1002/jrs.4666
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of proton order of thin ice Ih film

Abstract: The polarized Raman spectra of the upper part of a thin ice Ih film were obtained in the range of 150 cm−1 to 3800 cm−1. The spectra showed clear polarization dependence; several new peaks were also observed. The longitudinaloptic–tranverseoptic (LO–TO) splitting of the mode near 220 cm−1 in the translational vibration region was experimentally confirmed at 133 K. The Fermi resonance between the bending overtone (around 3270 cm−1) and symmetry stretching fundamental (around 3350 cm−1) in the stretching vibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Their results showed that ice XI (i.e. proton‐ordered phase of ice Ih) slowly formed in the upper part of a thin ice Ih film without KOH as the temperature gradually decreased below 133 K . Talkenberger et al .…”
Section: Solid‐state Studiesmentioning
confidence: 67%
See 1 more Smart Citation
“…Their results showed that ice XI (i.e. proton‐ordered phase of ice Ih) slowly formed in the upper part of a thin ice Ih film without KOH as the temperature gradually decreased below 133 K . Talkenberger et al .…”
Section: Solid‐state Studiesmentioning
confidence: 67%
“…Their results showed that ice XI (i.e. proton-ordered phase of ice Ih) slowly formed in the upper part of a thin ice Ih film without KOH as the temperature gradually decreased below 133 K. [135] Talkenberger et al performed Raman spectroscopic investigations of epitaxial BiFeO 3 thin films on rare earth scandate substrates. Their results were supported by symmetry-based calculations including the analysis of Raman scattering geometry as well as the dielectric function of BiFeO 3 in the IR range.…”
Section: Single Crystalsmentioning
confidence: 99%
“…To quantify, we calculated the A 3090 /A 3210 (peak area ratios) ratio through multi‐peak fitting for each spectrum, and compared these ratios in Figure 5b. The results clearly indicate a reduction in the A 3090 /A 3210 ratio upon the introduction of these additives, signifying a disruption to the pristine microstructure of the ice Ih phase [49] . Notably, DEE demonstrated the least impact on the ice's microstructure among the tested additives while EG had the most destructive power.…”
Section: Resultsmentioning
confidence: 91%
“…The results clearly indicate a reduction in the A 3090 /A 3210 ratio upon the introduction of these additives, signifying a disruption to the pristine microstructure of the ice Ih phase. [49] Notably, DEE demonstrated the least impact on the ice's microstructure among the tested additives while EG had the most destructive power.…”
Section: Methodsmentioning
confidence: 95%